Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Android Pada Materi Dimensi Tiga Kelas X SMA - Doni Dwiranata; Dewi Pramita; Syaharuddin Syaharuddin (Jurnal Varian, 2019)
Abstract: This study aims to develop and produce android-based mathematics learning media on the subject of three dimensions of point, line, and field positions in space, for class X high school students and find out the validity, effectiveness, and practicality of interactive multimedia-based learning media. This type of research is a research development in the form of a three dimensional interactive learning media. Media development refers to the ADDIE development model which includes 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. The subjects of this study were students of class X IPA and students of class X IPS SMA Negeri 1 Maronge. The instruments used in this study were questionnaire validation of material experts and media experts, student questionnaire responses, and student evaluation tests. The results of the development research are: (1) The results of the validation of the material and the media obtain an average score of 36 with the category "quite valid"; (2) The results of the effectiveness of the media in small group trials have achieved 100% mastery learning in the "very effective" category; (3) The results of the practicality of the media in small group trials obtained an average score of 57 in the "very practical" category; (4) The results of the effectiveness of the media in large group trials gained mastery learning reaching 80% with the category of "effective"; and (5) The practicality of the media in the large group test obtained an average of 54,485 in the "practical" category.